2012
DOI: 10.1111/j.1463-1326.2012.01557.x
|View full text |Cite
|
Sign up to set email alerts
|

Liraglutide: short‐lived effect on gastric emptying—long lasting effects on body weight

Abstract: The data suggest that the 'gastric inhibitory' GLP-1 receptors in rats are subject to desensitization/tachyphylaxis but that this effect is dependent on full 24-h exposure as obtained by liraglutide. The body weight-lowering effects of GLP-1 receptor stimulation are not subject to desensitization. These data indicate that regulation of appetite signals in the brain, and not GE, is the main mechanism for liraglutide-induced weight loss.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
134
3
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 154 publications
(152 citation statements)
references
References 48 publications
11
134
3
4
Order By: Relevance
“…Liraglutide has a half life of 13 hours, and is therefore dosed once daily without regard to meals. A rodent study suggests that the effect of liraglutide to slow gastric emptying is not sustained over time, and that regulation of appetite signals in the brain is the main mechanism for liraglutide induced weight loss [38]. In contrast, this study showed that gastric emptying is slowed for a longer period of time with exenatide, suggesting that this mechanism may be more important for exenatide's effect to reduce weight.…”
Section: Glp-1 Receptor Agonistscontrasting
confidence: 52%
“…Liraglutide has a half life of 13 hours, and is therefore dosed once daily without regard to meals. A rodent study suggests that the effect of liraglutide to slow gastric emptying is not sustained over time, and that regulation of appetite signals in the brain is the main mechanism for liraglutide induced weight loss [38]. In contrast, this study showed that gastric emptying is slowed for a longer period of time with exenatide, suggesting that this mechanism may be more important for exenatide's effect to reduce weight.…”
Section: Glp-1 Receptor Agonistscontrasting
confidence: 52%
“…Moreover, nausea scores did not differ between treatments. In addition, although it has been shown that liraglutide exerts a short-term reduction in gastric emptying, this effect is markedly diminished after short-term repeated dosing of liraglutide, whereas the body weight loss continues (34). Results from other studies with GLP-1RA treatment also provide arguments against nausea or delayed gastric emptying as explanations for the appetite-and body weightreducing effects of GLP-1RA treatment.…”
Section: Resultsmentioning
confidence: 66%
“…GE in healthy individuals exhibits a wide interindividual variation of~4-17 kJ/min (~1-4 kcal/min) [14]; this is increased in diabetes because of the high prevalence of delayed [15], and occasionally rapid, GE [16]. The reduction in postprandial glucose following acute administration of GLP-1 [17][18][19] or 'short-acting' GLP-1 agonists [20,21] relates primarily to slowing of GE but clinical studies relating to the effects of GLP-1 and its agonists on BP have not discriminated between effects on fasting vs postprandial BP.…”
Section: Introductionmentioning
confidence: 99%